Vacancy-donor complexes in highly n-type Ge doped with As, P and Sb. (28th June 2016) - Kujala, J; Südkamp, T; Slotte, J; Makkonen, I; Tuomisto, F; Bracht, H
Abstract: Positron annihilation spectroscopy was performed to study defects in Ge doped with As, P and Sb. In each case, the samples had approximately the same dopant concentration  ̃10 19 cm −3 . Results from the Doppler broadening and positron lifetime spectroscopies were compared to electronic structure calculations. The positron lifetime results show that the open volume related to the defect centers is not larger than a monovacancy. The results suggest that in the As doped sample the dominant trap at room temperature is a complex consisting of a vacancy and at least three dopant atoms. In the case of P doped Ge the results indicate that two defect complexes compete in positron trapping. Complexes with a higher number of P atoms around the vacancy seem to dominate at room temperature whereas at low temperature positron trapping at centers with fewer P atoms around the vacancy becomes more significant. The complexes with fewer P atoms are more negatively charged. In Sb doped Ge the results suggest that several types of traps are simultaneously competing in positron trapping at all measurement temperatures.